The Applicability of Sanctions on Corporate Organisations under OHADA Law in Cameroon (African Journal of Law and Politics, 2025)
This article discusses the applicability of sanctions on corporate bodies under OHADA law in Cameroon.Corporate entities are fictional or artificial entities created by the law, it is on this basis that we seek toaddress the problem of sanctioning corporation in a bijural system like the case of Cameroon. TheCameroonian law makers have put in place legislations with regards to sanctions that are imposed oncorporate entities with some differences at the level of interpretation and applicability due to the bijuralsystem applicable in the country. The doctrinal method has been employed which include primary andsecondary sources of data, primary source of data consist of laws and legislations made in the country whilesecondary data consist of books, journals and legal writings with regards to Company Law in Cameroon. Itis on this basis that this article analyses how corporate sanctions are imposed within the bijural legal systemof Cameroon. The approaches employed by these two legal systems in the applicability of the laws are notactually accepted by those in the Common Law jurisdiction for lack of precisions in the law by thoseconcerned. As to the realities of the day-to-day occurring in Cameroon, it is proposed that the Cameroonianlegislators should enact precedes laws in sanctioning corporate bodies and also to harmonize its own lawswith regard to corporate laws so as to meet with the aspirations of the present reality.